Prinsip Maṣlaḥah dalam Penyelesaian Sengketa Tanah Adat: Kajian terhadap Praktik Musyawarah Adat Dayak Kenyah di Desa Pampang - Hamid, Adnan; Syahrina R, Nurul Ain (STAINI Press, 2025)
This study aims to analyze the application of the maṣlaḥah principle in the dispute resolution mechanism of customary land among the Dayak Kenyah community in Pampang Village, Samarinda. This issue is significant because customary land functions not only as an economic asset but also as a source of identity, spirituality, and cultural sustainability. The maṣlaḥah approach in Islamic law offers an ethical framework that aligns with the communal justice and social harmony values upheld by indigenous communities. This research employs a qualitative method with a normative-empirical approach. Data were collected through the study of legislation, customary documents, interviews with traditional leaders, and direct observation of customary deliberation practices. The analysis connects the principles of maṣlaḥah mursalah and Islamic social justice theory with the indigenous dispute resolution practices that emphasize deliberation, consensus, and the balance of collective interests. The findings reveal that the Dayak Kenyah customary dispute resolution mechanism reflects maṣlaḥah values, particularly in maintaining collective welfare, preventing social division, and ensuring proportional justice distribution. However, its effectiveness remains limited due to the lack of formal recognition of customary decisions. This study recommends integrating the outcomes of customary deliberations into the national legal system to strengthen legal certainty and promote social justice based on maṣlaḥah values.